ANALISIS KETERAMPILAN METAKOGNITIF DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PROGRAM STUDI KEWIRAUSAHAAN UNIVERSITAS AUFA ROYHAN - Siregar, Yulia Pratiwi (Universitas Aufa Royhan, 2022)
This study aims to describe the metacognitive abilities of students in the Entrepreneurship Study Program. The metacognitive ability of students described in the study is the metacognitive ability of students with high, medium, and low academic abilities to solve mathematical problems in students of the entrepreneurship study program. This research was conducted by applying the qualitative method. The informants in this study were the Head of the Study Program and 8 students who were taken using the Total Sampling technique. Data collection techniques used field notes, tests, interviews, and documentation. Data analysis was carried out using data reduction. The results showed (1) students who had high mathematical ability had very good mathematical problem solving abilities, (2) students who had moderate mathematical ability had good mathematical problem solving abilities, and (3) students who had low mathematical ability had sufficient mathematical problem solving.